Robot Publicitario Aplicado A La PedagogÃa Infantil - BuenaÃ±o, Gladys Urquizo; Gavilanes, Javier; Vaca, Isabel; VillagÃ³mez, Leonela; Llerena, Angel (European Scientific Journal, ESJ, 2018)
This paper focuses on presenting the design and build up of an interactive didactic robot. Its structure has an omnidirectional traction with WIFI communication for sending and receiving information between the user and the robot. Its structure is made up of two screens: one on the top of the robot, simulating a head, and another one on the front of its figure. It has a camera to obtain "vision" and proximity sensors to create a symbiosis relationship with the user. To control the devices, a Raspberry Pi 3 and an Arduino 328 card were used under a master slave system. The structure of the robot was designed using a 3D modeling, and the parts were created using a 3D printing. It has the following functions: manual control, tell a story, dance, advertising or game modes that can be selected from the user interface. This prototype places an emphasis on presenting applications that stimulate learning and logical understanding in children, leaving the possibility of being reprogrammed to add functions.